An account for barriers and strategies in fulfilling women's right to quality maternal health care: a qualitative study from rural Tanzania - Thomas Wiswa John; Dickson Ally Mkoka; Gasto Frumence; Isabel Goicolea (BMC, 2018)
Abstract Background Tanzania has ratified and abides to legal treaties indicating the obligation of the state to provide essential maternal health care as a basic human right. Nevertheless, the quality of maternal health care is disproportionately low. The current study sets to understand maternal health services' delivery from the perspective of rural health workers', and to understand barriers for and better strategies for realization of the right to quality maternal health care. Methods Semi-structured in-depth interviews were conducted, involving 11 health workers mainly; medical attendants, enrolled nurses and Assistant Medical Officers from primary health facilities in rural Tanzania. Structured observation complemented data from interviews. Interview data were analyzed using thematic analysis guided by the conceptual framework of the right to health. Results Three themes emerged that reflected health workers' opinion towards the quality of health care services; "It's hard to respect women's preferences", "Striving to fulfill women's needs with limited resources", and "Trying to facilitate women's access to services at the face of transport and cost barriers". Conclusion Health system has left health workers as frustrated right holders, as well as dis-empowered duty bearers. This was due to the unavailability of adequate material and human resources, lack of motivation and lack of supervision, which are essential for provision of quality maternal health care services. Pregnant women, users of health services, appeared to be also left as frustrated right holders, who incurred out-of-pocket costs to pay for services, which were meant to be provided free.